A genetic study of summer eczema in Icelandic horses - Lindberg, Louise (2006)
Several horse breeds around the world have shown sensitivity to biting insects. The horses seem to be particularly sensitive to certain species of the genus Culicoides. The main reaction to the insects' bites is itchiness and some horses itch until wounds appear. In Sweden and the rest of Europe many breeds have been observed to have the problem and as regards Icelandic horses this phenomena is widely discussed. It has been shown that horses exported from Iceland to continental Europe as adults have higher disease prevalence. These horses have less chance to develop a normal immune defense to Culicoides, since no Culicoides have been found in Iceland. Nevertheless, a certain proportion of Icelandic horses born outside Iceland are also affected by the disease, which in Sweden is known as summer eczema.